Optimizing repeat liver transplant graft utility through strategic matching of donor and recipient characteristics. Issue 11 (November 2015) - Hung, Kenneth; Gralla, Jane; Dodge, Jennifer L.; Bambha, Kiran M.; Dirchwolf, Melisa; Rosen, Hugo R.; Biggins, Scott W.
<x xml:space="preserve">Abstract</x> Repeat liver transplantation (LT) is controversial because of inferior outcomes versus primary LT. A minimum 1‐year expected post–re‐LT survival of 50% has been proposed. We aimed to identify combinations of Model for End‐Stage Liver Disease (MELD), donor risk index (DRI), and recipient characteristics achieving this graft survival threshold. We identified re‐LT recipients listed in the United States from March 2002 to January 2010 with > 90 days between primary LT and listing for re‐LT. Using Cox regression, we estimated the expected probability of 1‐year graft survival and identified combinations of MELD, DRI, and recipient characteristics attaining >50% expected 1‐year graft survival. Re‐LT recipients (n = 1418) had a median MELD of 26 and median age of 52 years. Expected 1‐year graft survival exceeded 50% regardless of MELD or DRI in Caucasian recipients who were not infected with hepatitis C virus (HCV) of all ages and Caucasian HCV‐infected recipients <50 years old. As age increased in HCV‐infected Caucasian and non‐HCV‐infected African American recipients, lower MELD scores or lower DRI grafts were needed to attain the graft survival threshold. As MELD scores increased in HCV‐infected African American recipients, lower‐DRI livers were required to achieve the graft survival threshold. Use of high‐DRI livers (>1.44) in HCV‐infected recipients with a MELD score > 26 at re‐LT failed to achieve the graft survival threshold with recipient age ≥ 60 years (any race), as well as at age ≥ 50 years for Caucasians and at age < 50 years for African Americans. Strategic donor selection can achieve >50% expected 1‐year graft survival even in high‐risk re‐LT recipients (HCV infected, older age, African American race, high MELD scores). Low‐risk transplant recipients (age < 50 years, non‐HCV‐infected) can achieve the survival threshold with varying DRI and MELD scores. Liver Transpl 21:1365‐1373, 2015. © 2015 AASLD.